Sustainability transformation: The role of accountancy and finance professionals in the Singapore manufacturing sector - WANG, Jiwei (Institutional Knowledge at Singapore Management University, 2023)
Sustainability is already reshaping the Singapore manufacturing sector. The majority of companies surveyed (70%) have started their sustainability transformation in one form or another, and many have initiated discussions. However, on the whole, only 37% of companies have implemented sustainability initiatives, and 21% have reported on sustainability. On the bright side, these percentages are slated to double within 1-3 years. The infusion of sustainability into the manufacturing sector has led to accountancy and finance professionals potentially playing a bigger role in their organisations, particularly in aligning the sustainability objectives with business strategies. The study notes that manufacturing companies are mostly focusing their sustainability efforts on six areas: (1) circular economy, (2) reducing greenhouse gas emissions, (3) renewable energy and energy efficiency, (4) preventing pollution, (5) sustainability reporting, and (6) sustainable finance. Corporate governance for sustainability and sustainability data management are also emerging areas of focus. From the findings, the researchers distilled 10 sustainability skills for sustainability transformation for the manufacturing sector: (1) stakeholder and community engagement, (2) circular economy and resource efficiency, (3) carbon and decarbonisation strategies management, (4) sustainability data management and impact measurement, (5) sustainability reporting, (6) sustainability risk management, (7) sustainable finance, (8) internal audit on sustainability governance, (9) climate and nature financial implication quantification, and (10) natural capital management.